Proceedings of the 32nd International Technical Meeting of the Satellite Division of the Institute of Navigation (ION GNSS+ 201 2019
DOI: 10.33012/2019.16864
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dual-frequency Signal Quality Monitor to Support CAT II/III GBAS

Abstract: BIOGRAPHY (IES) Junesol Song is a postdoctoral fellow in Telecom laboratory at the Ecole Nationale de l'Aviation Civile (ENAC) in Toulouse, France. She received B.S. and Ph.D. degrees in aerospace engineering from Seoul National University, South Korea. Her research interests include dual-frequency/multi-constellation GBAS fault monitoring, multi-GNSS Network RTK, Compact RTK, carrier phase-based algorithms and positioning, and remote sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Furthermore, as described in [9] there are several different penalty functions, such as the death penalties, the static penalties, dynamic penalties, or adaptive penalties, that can be used. The death penalties are the simplest functions possible as they reject any unfeasible solutions by penalizing them with infinity.…”
Section: Optimization-based Data Collect Planning Penalty Methods Ove...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as described in [9] there are several different penalty functions, such as the death penalties, the static penalties, dynamic penalties, or adaptive penalties, that can be used. The death penalties are the simplest functions possible as they reject any unfeasible solutions by penalizing them with infinity.…”
Section: Optimization-based Data Collect Planning Penalty Methods Ove...mentioning
confidence: 99%
“…In order to protect a Civil Aviation user from a Hazardous Misleading Information (HMI) created by a non -nominal GNSS signal distortion [1], specific monitors, called Signal Quality Monitors, are implemented in SBAS (Satellite Based Augmentation System) [4], [6] and GBAS (Ground Based Augmentation System) [8], [9] systems. These monitors are based on the combining of different correlator outputs computed by the fixed SBAS/GBAS reference station receiver in order to detect the presence of signal distortions on the correlation function.…”
Section: Introductionmentioning
confidence: 99%
“…Since Galileo E1c signal has the same chipping rate as that of GPS L1 C/A signal, the Honeywell monitor can be used without any modification even if the different modulations are used: Binary Phase Shift Keying (BPSK) for GPS L1 C/A and Composite Binary Offset Carrier (CBOC). However, GPS L5 and Galileo E5a signals, which are modulated as BPSK (10), have a 10 times larger chipping rate, therefore, the code offset ranges for taking correlator outputs and its interval are increased to the factor ten of the values used for GPS L1 C/A and Galileo E1c signals. That is, the Honeywell monitor uses the correlator outputs at locations ranged from -0.5 to 1.25 chips in this study.…”
Section: Monitors For Signal Deformation Faultsmentioning
confidence: 99%
“…The TM parameters used in this study is shown in Table 3 and Table 4. The threat models stemmed from [10] for these modernized signals are currently being discussed for standardization. Here, we use x min :Δx: In the second step, the correlation function is computed using the generated code sequence.…”
Section: Fig 8-diagram Of the Fault Generation Processmentioning
confidence: 99%
See 1 more Smart Citation